Adverse Cerebral Cardiovascular Events Associated With Checkpoint Kinase 1 Inhibitors: A Systemic Review. Issue 5 (May 2021) - Yang, Tongtong; Gu, Jie; Du, Chong; Shan, Tiankai; Wei, Tianwen; Li, Yafei; Wang, Liansheng
Abstract : Abstract: Checkpoint kinase 1 (CHK1) plays a broad role in regulating the cell cycle process and is involved in the pathogenesis of various malignant tumors. Preclinical and animal studies have shown that CHK1 inhibitors can enhance the cytotoxic effects of radiotherapy and chemotherapy. Currently, CHK1 inhibitors are actively tested in clinical trials. Nonspecific adverse cerebral cardiovascular events were reported after CHK1 inhibitor use; these events need to be monitored and managed carefully during the clinical application of CHK1 inhibitors. To get a better understanding of these, noteworthy adverse cardiovascular events, we systemically searched the PubMed, Cochrane databases, and clinicaltrials.gov, for relevant clinical trials and case reports. A total of 19 studies were identified and included in this review. Among the reported cerebral cardiovascular events, the most common is incident abnormal blood pressure fluctuations (n = 35), followed by incident QTcF prolongation (n = 15), arrhythmia (n = 13, 3 atrial fibrillation and 10 bradycardia), thromboembolic events (n = 9, 6 pulmonary embolisms, 2 stroke, and 1 cerebrovascular event), cardiac troponin T elevation (n = 2), and ischemic chest pain (n = 2). Besides, the estimated incidence for overall cardiovascular events based on the available data is 0.292 (95% confidence interval: 0.096–0.488). CHK1 inhibitors administered in tumor patients on top of conventional therapies can not only enhance the antitumor effects, but also induce adverse cerebral cardiovascular events. It is, therefore, of importance to carefully monitor and manage the CHK1 inhibitor–induced adverse effects on the cerebral cardiovascular system while applying CHK1 inhibitors to tumor patients. Abstract : Supplemental Digital Content is Available in the Text.